Answer:
See Explanation
Step-by-step explanation:
The question is incomplete as g(x) is not properly written.
I'll assume the following:
[tex]f(x) = 3x^2 - 15[/tex]
[tex]g(x) = 1- 2x[/tex]
Required
Determine (f o g)(-6)
In functions:
(f o g)x = f(g(x))
So:
[tex](f o g)(-6) = f(g(-6))[/tex]
First, we calculate g(-6)
[tex]g(x) = 1- 2x[/tex]
[tex]g(-6) = 1 - 2*-6[/tex]
[tex]g(-6) = 13[/tex]
Substitute 13 for g(-6) in [tex](f o g)(-6) = f(g(-6))[/tex]
[tex](f o g)(-6) = f(13)[/tex]
Next, we calculate f(13)
[tex]f(x) = 3x^2 - 15[/tex]
[tex]f(13) = 3 * 13^2 - 15[/tex]
[tex]f(13) = 3 * 169 - 15[/tex]
[tex]f(13) = 492[/tex]
Hence:
[tex](f o g)(-6) = 492[/tex]
Use the above analysis and explanation to answer your question